2012
DOI: 10.1021/es300022c
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Contamination and Diarrheal Pathogens on Surfaces and in Soils among Tanzanian Households with and without Improved Sanitation

Abstract: Little is known about the extent or pattern of environmental fecal contamination among households using low-cost, on-site sanitation facilities, or what role environmental contamination plays in the transmission of diarrheal disease. A microbial survey of fecal contamination and selected diarrheal pathogens in soil (n = 200), surface (n = 120), and produce samples (n = 24) was conducted in peri-urban Bagamoyo, Tanzania, among 20 households using private pit latrines. All samples were analyzed for E. coli and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
184
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(202 citation statements)
references
References 38 publications
12
184
4
2
Order By: Relevance
“…This finding is consistent with those of Pickering and others who found diarrheagenic E. coli in the soil of household compounds in rural Tanzania. 42 We suspect this fecal contamination was from domestic animals that were present in household compounds and from improper disposal of feces from child defecation events. In a nested sub-study, we found that only 14% of feces from study children was disposed of in the toilet and that the majority (74%) was disposed of in a nearby field or waste ditch (Christine Marie George, personal communication).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with those of Pickering and others who found diarrheagenic E. coli in the soil of household compounds in rural Tanzania. 42 We suspect this fecal contamination was from domestic animals that were present in household compounds and from improper disposal of feces from child defecation events. In a nested sub-study, we found that only 14% of feces from study children was disposed of in the toilet and that the majority (74%) was disposed of in a nearby field or waste ditch (Christine Marie George, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26]42 However, despite this growing evidence base, interventions to intervene upon this exposure route for pediatric populations are nonexistent. Furthermore, we found that in our study population that caregivers do little to prevent children from putting soil in their mouth.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] High concentrations of fecal indicator bacteria (FIB) and pathogens can be in food, water, soil, and on hands and surfaces. 3,5 Elevated levels of fecal contamination in the environment are attributed to inadequate sanitation, a leading cause of child morbidity and mortality from diarrheal diseases, malnutrition, and stunting. 6 In addition, fecal contamination on surfaces is linked to increased risk of diarrheal disease, as highlighted by a study at a child care center in the United States.…”
mentioning
confidence: 99%
“…Surface decontamination may be important, as, for example, one study from Tanzania showed dinner plates were readily contaminated with FIB and gastrointestinal pathogen markers in peri-urban households. 3 In this study, we examined household cleaning practices and the prevalence of FIB (e.g., total coliform, enterococci, and Escherichia coli) on dinner plates as indicators of the need for improved cleaning practices (e.g., surface disinfection using bleach) in four peri-urban communities near Iquitos, Peru. We also estimated the rate of new household demand for bleach for domestic disinfection using the conceptual model of adoption stages and behavioral indicators of a new demand for sanitation developed by Jenkins and Scott (2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation